FREKUENSI PENIMBANGAN DENGAN STATUS GIZI BALITA - Aswita Amir; Siti Nur Rochimiwati; Ramlan Asbar; Riana Arfani Toro (Media Gizi Pangan, 2017)
Background: Nutritional status is a measure of the state of the body based on food consumption and the use of nutrients in the body. The monthly growth monitoring activities performed every month in Posyandu by looking at the growth monitoring through KMS, healthy childrens will show Weight gain every month follows the growth line and provides information on the nutritional status of children because the parents and children's visit is actively expected to help the parents in stimulating the development of children, but on the other hand the parent activity can make the parents become inactive in the visit to Posyandu.Objectives: The study objective was to analyze the relation between the frequency of weighing with nutritional status of children.Methods:  The samples was children aged 06-59 month which  amount 107 people obtained by using simple random sampling technique. Frequeny of weighing was known from the questionnaire which has been filled by the respondent and matched with KMS or Posyandu notebook. Children nutritional status was calculated by using WHO Anthro 2005 based on index of BB/U. This study used chi square test with SPSS program and the data was presented in the form of frequency distribution tables and narratives.Results:  The result of study showed that 55.1% of samples had a frequency of weighing ≥ 4 times. Sample with good nutritional status equal to 77,6%. The result of statistical test with ρ value 0,079 (ρ> 0,050) shows that there is no relation between frequency of weighing with nutritional status of children.Conclusions: There is no relation between frequency of weighing and nutritional status of children.Keywords: frequency of weighing, nutritional status, children